A new numerical framework for large-eddy simulation of waves generated by objects piercing water surface. Issue 2 (March 2019) - Yang, Zixuan; Cui, Zuo; Wang, Shizhao
Highlights: This article belongs to Fluid Mechanics Abstract: A novel numerical framework is developed for large-eddy simulation (LES) of interactions among air, water, and solid bodies. The motions of air and water are solved on a fixed block-structured mesh, with the air–water interface captured using the volume-of-fluid method. A new sub-grid scale stress model based on the vortex identifier is used to improve the robustness and efficiency of the simulation flows with air–water interface. The new framework is tested in the context of bow waves and Kelvin waves generated by a water-surface vehicle. Wave breaking at the bow of the vehicle is captured in LES. The LES results of wave geometry approaches the measurements progressively as the grid resolution is refined. The simulation results indicate that LES is a useful tool for studying wave dynamics of water-surface vehicles.